The Correlation between Serum Growth Differentiation Factor-15 Levels and Post-Acute Myocardial Infarction Acute Heart - Kenny Mayavani; JB. Suparyatmo; Dian Ariningrum (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
Acute Heart Failure (AHF) is a common rapid complication of Acute Myocardial Infarction (AMI). Myocardial dysfunction leads to pathologic remodeling of the heart, which causes AHF. Growth differentiation factor-15 (GDF-15) is expressed by cardiomyocytes and upregulated due to injury and cardiomyocyte damage. Thus, it can be used as a predictor of severe heart damage. This study aimed to determine the correlation between GDF-15 levels and the incidence rate of post-AMI AHF. This prospective cohort study was performed in patients with AMI treated in Dr. Moewardi Hospital from August to September 2019. The Kolmogorov-Smirnov normality test was used. Bivariate analysis was applied for Hazard Ratio (HR) with 95% CI. The GDF-15 cut-off used the ROC curve. The Cox Regression Proportional Hazard Model was used for multivariable analysis. The significance value was p <0.05. During the study, there were a total of 74 subjects. Bivariate analysis showed significant correlation between serum GDF-15 levels and hypertension history to the incidence of post-AMI AHF [HR=3.259; 95%CI (1.1558–6.819); p=0.002] and [HR=3.293; 95%CI (1.489-7.282); p=0.003]. Multivariate analysis showed that both variables had a similar strength of the correlation. The risk and the incidence rate of AHF were three times higher in AMI subjects with a history of hypertension and elevated GDF-15 levels. High serum GDF-15 levels and a history of hypertension can be predictors of post-AMI AHF.